PENINGKATAN PEMBELAJARAN BERBICARA DENGAN MENGGUNAKAN METODE LEARNING COMMUNITY (KOMUNITAS BELAJAR) PADA SISWA KELAS IXB SMP NEGERI 19 PALU - Aminah S.S., M.Pd. (Balai Bahasa Sulawesi Tengah, 2018)
This study aims to describe the improvement of learning to speak by using the method of learning community (study group) in the students of class IXB SMP Negeri 19 Palu in the planning, implementation and assessment phase. The approach used in this research is qualitative descriptive approach. This type of research is a classroom action research. The data of this study were taken through tests and nontes. Data were analyzed quantitatively and qualitatively. The result of the research shows that (1) this planning is done in collaboration with the teacher in preparing the lesson plan and the planning of language learning on the speaking skill aspect by using the learning community method on the aspect or criteria of speech assessment (the accuracy of speech, grammar, word choice, mastery of topics, voice volume, and gestures and mimics, (2) the implementation of cycle I, there are still many activities of students and teachers have not been done maximally.In the second cycle of learning to speak increased during the learning process, and (3) the evaluation results learning to speak through the application of learning community method (learning community) showed improvement.The results of speech test analysis showed that in the first cycle average value of 45 and including very low category increased in cycle II, that is with an average value of 74 and including the high category.As for the percentage results an increase of 29%. Keywords: Learning, Speaking, Methods Learning Community (Community Learning) Students Class IXB SMP Negeri 19 Palu